Quantitative protein expression of Malaysian Phaleria macrocarpa - Muhamad Bunnori, Noraslinda; Hamdan, Nurul Ashima; Abu Hassan, Muhamad Shafiq; Mohamed Rehan, Aisyah; Abd Halim, Khairul Bariyyah; Haron, Normah (World Research Library, 2018)
Herbal plants are the best alternative for synthetic medicines which are costly and proved to be double-edged source. P. macrocarpa is the traditional herb compatible in curing diseases like diabetes, inflammation, and even cancer. People have gained lots of benefits from most parts of the plant with largest usage of seeds. This study aimed to analyze protein expressions in three major parts of the plant; leaf, seed and fruit by using SDS PAGE and high-throughput two-dimensional gel electrophoresis as proteomics approached. There were 42 spots detected in a pH range of 3-10 with 3 spots have been analyzed by MALDI-TOF mass spectrometry. Most identified proteins were expressed in seeds with highest intensity of bands and spots. The identified spots are homologs to putative clathrin assembly protein and ferredoxin-NADP+ reductase which are characterized as ‘housekeeping agent’ in plant system.